MANAJEMEN PEMBIAYAAN DALAM MENINGKATKAN MUTU PENDIDIKAN DI UNIVERSITAS DEHASEN BENGKULU - - Suwarni (UNIVED Press, 2015)
Suwarni; The purpose of this study was to determine objectively and depth of policy and implementation of financial management in particular in relation to the financing of education quality improvement. The method used in this research is descriptive research method is a method in researching the status of groups of people, one object, one condition, with a system of thought or one class of events in the present. The results achieved in the quality of education in the University Dehasen Bengkulu, although the implementation of the financing has not run optimally, does not mean not having good results. The delivery of the results achieved; competence of graduates is very supportive in the world of work, have a good work ethic, and have a high motivation to continue their education to a higher level. Key words: Financial Management, Quality Of Education